COMBUSTION PROCESS OF COTTON FIBER IN PNEUMATIC TRANSPORT: MODELING THE TIME FROM IGNITION TO COMPLETE COMBUSTION (Web of Technology: Multidimensional Research Journal, 2024)
This article models the combustion process of cotton fiber within pneumatic transport systems in cotton mills. It analyzes how a spark can quickly spread through the airflow, potentially igniting the cotton fiber and posing a safety hazard. Based on a mathematical model, the spread time of the combustion process and the impact of airflow parameters were determined. A simulation conducted in MATLAB illustrates the propagation speed of the combustion front along the pipe, total time, and temperature variations through graphical representations. This model has practical significance in assessing combustion risks and implementing safety measures.